Progress in the classical biological control of Agrilus planipennis Fairmaire (Coleoptera: Buprestidae) in North America. Issue 3 (12th May 2015) - Bauer, Leah S.; Duan, Jian J.; Gould, Juli R.; Van Driesche, Roy
Abstract: First detected in North America in 2002, the emerald ash borer (EAB) ( Agrilus planipennis Fairmaire; Coleoptera: Buprestidae), an invasive phloem-feeding beetle from Asia, has killed tens of millions of ash ( Fraxinus Linnaeus; Oleaceae) trees. Although few parasitoids attack EAB in North America, three parasitoid species were found attacking EAB in China: the egg parasitoid Oobius agrili Zhang and Huang (Hymenoptera: Encyrtidae) and two larval parasitoids Tetrastichus planipennisi Yang (Hymenoptera: Eulophidae) and Spathius agrili Yang (Hymenoptera: Braconidae). In 2007, classical biological control of EAB began in the United States of America after release of these three species was approved. In 2013, release of the larval parasitoids was approved in Canada. Research continues at study sites in Michigan, United States of America where the establishment, prevalence, and spread of O. agrili and T. planipennisi have been monitored since 2008. However, establishment of S. agrili remains unconfirmed in northern areas, and its release is now restricted to regions below the 40th parallel. In 2015, approval for release of Spathius galinae Belokobylskij (Hymenoptera: Braconidae), an EAB larval parasitoid from the Russian Far East, may be granted in the United States of America. Researchers are guardedly optimistic that a complex of introduced and native natural enemies will regulate EAB densities below a tolerance threshold for survival of ash species or genotypes in forested ecosystems.